Estudo da influência de compostos recalcitrantes na remoção de matéria orgânica biodegradável no tratamento de efluente de refinarias de petróleo - Barros Júnior, Laerte de Medeiros (2008)
Petroleum Refinery wastewaters (PRW) have hart-to-degrade compounds, such as: phenols, ammonia, cyanides, sulfides, oils and greases and the mono and polynuclear aromatic hydrocarbons: benzene, toluene and xylene (BTX), acenaphthene, nitrobenzene and naphtalene. It is known that the microrganisms activity can be reduced in the presence of certain substances, adversely affecting the biological process of wastewater treatment. This research was instigated due the small number of studies regarding to this specific topic in the avaiable literature. This body of work ims to evaluate the effect of toxic substances on the biodegradability of the organic material found in PRW. Glucose was chosen as the model substrate due to its biodegradable nature. This study was divided into three parts: i) a survey of recalcitants compounds and the removal of phenol by using both biological and photochemical-biological processes; ii) biomass aclimation and iii) evaluation of the inhibitory effect certain compounds have on glucose biodegradation. The phenol degradation experiments were carried out in an activity sludge system and in a photochemical reactor. The results showed the photochemical-biological process to be more effective on phenol degradation, suggesting the superioruty of a combined photochemical-biological treatment when compared with a simple biological process for phenol removal from industry wastewaters. For the acclimation step, was used an activated sludge from industrial wastewaters. A rapid biomass aclimation to a synthetic solution composed of the main inhibitory compouns fpund in a PRW was obtained using the following operation condition: (pH = 7,0; DO ≥ 2,0 mg/L; RS = 20 days e qH = 31,2 and 20,4 hours), The last part was consisted of using respirometry evaluation toxicity effects of selected compounds over oxygen uptake rate to adaptated and non adaptated biomass in the presence of inhibitory compounds. The adaptated sludge showed greater degration capacity, with lower sensibility to toxic effects. The respirometry has proved to be very practical, as the techiniques used were simple and rapid, such as: Chemical Oxygen Demand (COD), Dissolved Oxygen (DO), and Volatile Suspended Solids (VSS). Using the latter it is possible to perform sludge selection to beggingthe process; thus allowing its use for aerobic treatment system`s behacior prediction